Alleviation of chilling injury in postharvest banana with protection materials - Lima, Juliana Domingues [UNESP]; Rozane, Danilo Eduardo [UNESP]; Gomes, Eduardo Nardini [UNESP]; Modenese Gorla da Silva, Silvia Helena [UNESP]; Kluge, Ricardo Alfredo (United Arab Emirates Univ, 2018)
Storage of bananas at low temperature is limited due to the development of chilling injury (CI). The purpose of this paper was to investigate the influence of different protection materials on occurrence of CI and the characteristics of banana in postharvest. Current paper also investigated temperatures variations in bags. The experiments were conducted with fruits of Musa spp., cultivars Prata (AAB) and Nanica (AAA). Comprised a completely randomized 2x3x6 factorial design, two cultivars, three temperatures (5 degrees C or 10 degrees C for 10 hours and 20 degrees C constant) and five protection materials (blue transparent polyethylene, white non-woven fabric, white opaque polyethylene, bubble wrap, white laminated non-woven fabric) and control (without protection). The different protection materials kept the temperature inside at 1 degrees C higher than environment. The critical temperature for occurrence of chilling injury was 5 degrees C for 'Prata' banana and 10 degrees C for 'Nanica' banana. White laminated non-woven fabric induced lower CI index and tended to maintain the peel color characteristics (L*, C* and h degrees) higher, compared to other protection materials. 'Nanica' fruits stored at 20 degrees C bagged with white laminated non-woven fabric exhibited lower incidence of Crown rot. Other physicochemical characteristics evaluated were not influenced by low temperature and protection material, only by cultivar.
Keywords: Bagging; Browning peel; Musa spp.; Low temperature; Storage